Diseño de planta para la producción de etanol carburante a partir de la caña de azúcar - Ramírez Lecca, Michael (2010)
In Chapter I, an analytical study is carried out on the Bioethanol Fuel market in Peru, with the purpose of estimating the demand for Bioethanol, as well as justifying the possibility of installing a chemical plant for this purpose. The present study was carried out based on statistical data related to the consumption of Fuel Bioethanol, basically taking into account the Regulation of the Law for the Promotion of the Biofuels Market, since as a product of recent insertion in the market it has little data of consumption. Plant capacity is for export. Chapter II, this chapter deals with the selection of process design, and aims to choose a type of manufacturing process from among the existing, which is the most convenient and adaptable to the plant. For this purpose, the different processes are shown highlighting their main characteristics for each one of them. These processes will be subject to an analysis of the technical-economic type. These will ultimately lead to the selection of the most appropriate process, which will govern the development of the project. Chapter III, Its purpose is to determine the choice of the most suitable place for the installation of the plant, for this purpose it makes use of the technique called balancing factors, which consists of assigning numerical values to the different primary and secondary factors. Chapter IV, Includes the design of the main equipment, such as distillation columns, pumps and tanks. For the design of the columns, the commercial simulator Hysys 3.0.1 is used, while for the case of pumps and tanks the spreadsheets are used in EXCEL. Chapter V, This chapter refers to the automatic control part, here the type of control to be used is defined, and it illustrates both the equipment and the controlled variables. Chapter VI, This chapter deals with process aids, such as the supply of water, water vapor, fuel and electricity; It also includes the storage facilities, security, buildings and laboratory. Chapter VII, He speaks to us about the distribution of the plant and basically defines the spatial arrangement of all the units of operation, for it the unitary and master plane was elaborated. Chapter VIII, This refers to safety and specifically some recommendations for corrective safety actions are given, as well as comments on the effluents discharged by the plant. Chapter IX, This chapter discusses the total investment, operating expenses and profitability, for this the spreadsheet was used. Chapter X, In this chapter the conclusions of the study are presented. Chapter XI, Shows the bibliographical references Chapter XII, In the appendix is presented, where chapters 2 and 4 are developed in detail